Recent progress and challenges of self-healing batteries - Zhonggui Quan; Xinyi Xiu; Meng Li; Li Song; Xuting Jin; Zhen Zhou (Energy Materials and Devices)
With the exponential growth of portable electronic devices and wearable technologies, batteries are currently required to deliver not only high energy density and extended cycling performance but also enhanced safety and exceptional durability. Inspired by the self-repair mechanism observed in natural systems, a self-healing strategy shows great application potential in enabling batteries to resist external physical and chemical damage. In this review, we provide a detailed exploration of the application of self-healing materials in battery components, including electrodes, electrolytes, and encapsulation layers. We also analyze the advantages and limitations of various self-healing mechanisms, highlighting their roles in optimizing battery performance. By presenting a comprehensive synthesis of existing research, the potential pathways for advancing the development of self-healing batteries are identified, as well as the key challenges and opportunities within this field. This review aims to promote the practical integration of self-healing batteries in smart and flexible electronic devices, paving the way for safer, more reliable, and long-lasting energy storage systems.